PEREMPUAN MUDA DI INTERNET: PENGALAMAN MENGHADAPI DAN MELAWAN KEKERASAN BERBASIS GENDER ONLINE - Desintha Dwi Asriani (UNIVERSITAS SEBELAS MARET (UNS), 2024)
This article focuses on the dynamics of young women's experiences in using internet-based technology amid the increasing trend of online gender-based violence (OGBV). This study deploys a qualitative approach, in which data collection is conducted through Forum Group Discussion (FGD) and in-depth interviews. Using feminist standpoint theory, women tending to be at risk of being victims become main informant. From their experiences, the meaningful information of how technology turns to be a new arena for the practice of violence against women could be identified. However, sociologically, based on the subaltern counterpublic perspective, the current study also shows that technology allows women to create safe spaces. Therefore, there is capacity of agentive practice that could be utilized to anticipate, respond to and resist the risk of OGBV, whether in the individual level or based on collective solidarity.